Emotional intelligence, prosocial behaviours, and coping responses in young adults: a conceptual framework for effective emotional regulation - Tee, Ker Shin; Ahmad, Nor Aniza; Roslan, Samsilah; Che Hassan, Norlizah (Human Resource Management Academic Research Society, 2023)
The traditional viewpoint on emotional disposition holds that emotions can increase a person's chances of success in adaptation and survival in the environment. Current study indicates that many Malaysian young adults, particularly undergraduate students, are vulnerable to emotional regulation difficulties such as stress, anxiety, and depression. University is a critical life-developmental event that lays the framework for young adults to discover their potential, beliefs, values, and interests. Entering higher education has a substantial impact on young adults' physical, psychological, cognitive, and emotional wellbeing. The current research shifts the emphasis of attention to provide a conceptual framework to guide more targeted intervention programs that may aid in the treatment of emotional regulation difficulties in young adults. Emotional intelligence, prosocial behaviours, and positive coping strategies may serve a homeostatic role by allowing the reduction of negative emotions and enhance the functioning coping strategies among young adults. The conceptual framework will employ existing literatures to demonstrate the interrelationships between emotional intelligence, prosocial behaviours, and coping responses, as well as explain how these components interact to predict young adults' emotional regulation. The conceptual framework guides the universities in reconsidering the needs of young adults and paving a new path for intervention programs to help young adults develop healthy emotional regulation skills.